A Novel Protocol For Enhancing The Security Of Electronic Transaction Using Gsm Authentication - Abu Bakar, Kamalrulnizam; Mahamoud, Abdirizak Omar; M. Azmi, Zafril Rizal (Penerbit UTM Press, 2006)
In fully developing the so-called information society, the use of new technologies for commercial transaction by electronic means and without the traditional paper support is increasingly common. This gives rise to the advantages of higher speed and lower costs in carrying out business activities, as well as the possibility of expanding the potential offers market for business. Secure Socket Layer/Transport Layer Security (SSL/TSL) protocol remain by far the most widely used means for providing security services for e-commerce transactions, despite the fact that these protocols were designed to provide security for communications links, and not for entire e-commerce transactions. Hence, does not support client authentication, which in turn makes certain frauds during online electronic transaction to take place. Though a large number of researches have been carried out in securing electronic transaction there is a lack of research been done in securing client authentication. This paper is to propose a different way of using the GSM Authentication to enhance the security of electronic transactions, which will also in return in increase the mobility when making an Internet transaction.